An Examination of Popular Family Publishing in the Republican Era: Aile Magazine (1947–1952) - Haykır, Handan (Kırşehir Ahi Evran Üniversitesi, 2026)
This study aims to examine the Aile Magazine, published between 1947 and 1952, within the framework of popular family publishing in the Republican era. The research comprehensively evaluates the magazine's literary and opinion pieces, stories and poems, and its coverage of family and child education, health, social values, art, and aesthetics. The findings show that the magazine's literary and opinion pieces encouraged readers to think critically, question their individual and social responsibilities, and reevaluate their relationship with modern life. In addition, articles on child and family education provided readers with practical guidance for daily life, while emphasizing the importance of family responsibilities, equality, and loving relationships. Through its content on folk culture, handicrafts, architecture, and history, the magazine contributed to the preservation of cultural heritage, the strengthening of aesthetic awareness, and the establishment of a bridge between the past and contemporary life. Special content for women and men supported the reshaping of social roles in the process of modernization and served to develop individuals' ethical and social responsibility awareness in the family and society. The magazine also served as a medium for developing the public's perception of cultural values, art, and aesthetics, increasing individual and social awareness through literary works, stories, poems, and opinion pieces. In these respects, Aile Magazine is not only a documentation of the cultural history of the early Republican era.

Bu çalışma, 1947–1952 yılları arasında yayımlanan Aile Dergisi’ni Cumhuriyet dönemi popüler aile yayıncılığı çerçevesinde incelemeyi amaçlamaktadır. Araştırma, derginin edebi ve fikir yazıları, hikâye ve şiir içerikleri, aile ve çocuk eğitimi, sağlık, toplumsal değerler, sanat ve estetik temalarını kapsamlı bir bakış açısıyla değerlendirmiştir. Bulgular, derginin edebi ve fikir yazılarının okuyucuyu eleştirel düşünmeye, bireysel ve toplumsal sorumlulukları sorgulamaya ve modern yaşamla ilişkilerini yeniden değerlendirmeye yönlendirdiğini göstermektedir. Ayrıca çocuk ve aile eğitimine dair yazılar, okurlara günlük yaşamda uygulanabilir rehberlik sağlarken, aile içi sorumluluk, eşitlik ve sevgi temelli ilişkilerin önemini vurgulamıştır. Halk kültürü, el sanatları, mimari ve tarih içerikleri aracılığıyla dergi, kültürel mirasın korunmasına, estetik bilincin güçlendirilmesine ve geçmişle çağdaş yaşam arasında bir köprü kurulmasına katkıda bulunmuştur. Kadın ve erkeklere yönelik özel içerikler ise toplumsal rollerin modernleşme sürecinde yeniden şekillenmesini desteklemiş, ailede ve toplumda bireylerin etik ve toplumsal sorumluluk bilincinin gelişmesine hizmet etmiştir. Dergi, aynı zamanda halkın kültürel değerler, sanat ve estetik algısını geliştiren bir mecra olarak işlev görmüş, edebî eserler, hikâyeler, şiirler ve fikir yazılarıyla bireysel ve toplumsal farkındalığı artırmıştır. Bu yönleriyle Aile Dergisi, yalnızca erken Cumhuriyet dönemi kültürel tarihinin belgelenmesi açısından önemli bir kaynak olmanın ötesinde, modernleşme sürecinin toplumsal yaşama ve günlük pratiklere yansımalarını gösteren, kültürel ve eğitimsel açıdan etkili bir yayın olarak değerlendirilebilir.
Erken Cumhuriyet Türkiye'sinde Popüler Aile Yayıncılığı Üzerine Bir İnceleme: Aile Dergisi (1947-1952)
Keywords: Historical Studies (Other); Tarihsel Çalışmalar (Diğer)